Text Analysis of Poem " Ibu" by D. Zamawi Imron in Indonesian Language High School’s Textbooks - Victorya Dumaris Saragih; M. Surif; Malan Lubis (Journal of Social Science, 2023)
This research aims to analyze one of the poems by D. Zamawi Imron to identify the relationship between readings and aspects that lie outside the readings. He told me about the creation of this poem. When he asked permission from his mother to go abroad to seek knowledge. The theory used is Critical Discourse Analysis modeled on Teun A. Van Dijk which has 3 dimensions: Reading Analysis, Social Cognition, and Social Analysis. There are also procedures used which are qualitative research procedures, with a critical paradigm. The object of this research was reading the poem "Ibu". Research information was obtained from an Indonesian language textbook for class X according to the 2013 curriculum. The research results included 3 AWK measures according to the van Dijk model: Reading analysis which has 3 aspects in it. On the macro structure, the poem has the theme of mother's love and sacrifice for her child and the child who wants to serve her mother. Superstructure, arrangement of stanza by stanza that alternates. Micro structure, which has detailed elements, intention, lexicon, metaphor, sentence form, and pronouns. Social cognition which deals with the poet's individual condition overrides his judgment of a child who shows love and affection to his mother. Evaluate Zamawi Imron's position, as well as how to control the events around him. Lastly is Social Analysis, where the bond between child and mother, the child realizes how much he misses his mother, how much love and sacrifice his mother gave him and the will of the child who wants to share the best service for his mother.